Cocrystals of Cefixime with Nicotinamide: Improved Solubility, Dissolution, and Permeability - Abulkhair Abdullah; Mutmainnah Mutmainnah; Erindyah R. Wikantyasning (Indonesian Journal of Pharmacy, 2022)
Cefixime is a third-generation cephalosporin antibiotic with poor solubility and permeability. The aim was to compared between Dry Grinding (DG) and Liquid-Assisted Grinding (LAG) methods to formed cocrystal of cefixime with nicotinamide. Cocrystal was prepared in 1:1 molar ratio and was characterizated by differential scanning calorimetry (DSC), fourier transform infra-red (FTIR), scanning electron microscopy (SEM), x-ray diffraction (XRD) methods. Cocrystal properties such as solubility, dissolution rate, and permeation rate were evaluated. The solubility test results obtained: 0.420 ± 0.016 (cefixime); 0.675 ± 0.016 (cocrystal 1:1 LAG); and 0.632 ± 0.016 (cocrystal 1:1 DG). The dissolution test results obtained: 186.55 ± 4.18 (cefixime); 232.83 ± 4.07 (cocrystal 1:1 LAG); and 228.82 ± 10.07 (cocrystal 1:1 DG). The permeability test results obtained: 153.58 ± 31.94 (cefixime); 306.22 ± 77.81 (cocrystal 1:1 LAG); and 211.44 ± 22.90 (cocrystal 1:1 DG). Cefixime can be formed into cocrystal with nicotinamide by DG and LAG methods according to the results of characterization using DSC, FTIR, SEM, and XRD accompanied by the increasing solubility, dissolution, and permeability. Cocrystal 1:1 LAG showed better result compared to cocrystal 1:1 DG.